(untitled) (Journal of the College of Basic Education, 2025)
The increasing number of students in a single classroom and the resulting diversity of individual differences have made it necessary for art education teachers to focus on various activities that suit the different levels of student comprehension. Teaching with the practical approach involves directly applying educational theories in the learning environment, which enhances student understanding and improves the acquisition of social skills. One of the most important advantages of this approach is the integration of theoretical and practical aspects, making it an effective tool for achieving educational goals in general. The research problem was defined as (the effect of teaching with the practical approach of puppet theater on the acquisition of social skills by primary school students). The research aimed to: Identify the effect of teaching with the practical approach of puppet theater on the acquisition of social skills by primary school students. The research objective was verified through the procedures in the third chapter, and the null hypothesis was tested, which stated: There are no statistically significant differences at the (0.05) level between the mean scores of the experimental group taught using the practical approach and the control group taught using the traditional method in the post-test of social skills acquisition by primary school students. The research population consisted of mixed primary schools in the General Directorate of Education in Diyala Governorate/Baqubah District Center, numbering (43) schools. The researcher randomly selected Al-Khamail Mixed Primary School, where (3) fifth-grade classes were available. Class (A) was chosen as the experimental group, with (50) students, and class (B) as the control group, with (52) students. Class (C), with (42) students, represented the pilot study sample. In the research procedures, a social skills assessment form was prepared, related to the study, which included (cooperation, empathy, effective communication with others, imitation and mimicry skills, self-assertion skills), which are partially related to puppet theater. To present the research results, the researcher used statistical methods to process the data with the statistical package (SPSS). The results showed: There are statistically significant differences at the (0.05) level between the mean scores of the experimental group taught using the practical approach and the control group taught using the traditional method in the post-test of social skills acquisition by primary school students. The study reached several conclusions, the most important of which is that focusing on the effective use of dialogue in puppet theater performances enhanced the role of learners in acquiring social skills (cooperation, empathy, effective communication with others, imitation and mimicry skills, self-assertion skills).